On Test Case Generation Satisfying the MC/DC Criterion - Kamal Z., Zamli; Al-Sewari, Abdul Rahman Ahmed Mohammed; Mohd Hafiz, Mohd Hassin (Soft Computing Research Group,UTM Malaysia (SCRG Publication), 2013)
Given the large domain of inputs and possibly too many possible execution paths, the software is often tested using a sampled set of test cases. A variety of coverage criteria have been proposed to assess the effectiveness of the sampled set of test cases. As far as structural testing involving predicate evaluation is concerned, criteria exercising aspects of control flow, such as statement,branch and path coverage have been the most common. Although useful, these criteria are often susceptible to the problem of masking. Addressing this issue, this paper explores to adoption of MC/DC as the necessary criteria for structural testing. Additionally, this paper also highlights the current state-of-the-art and identifies the strengths and limitations of existing work. Complementing existing work and in line with the current trends, this paper justifies on the development of a Harmony Search based test generation strategy for satisfying the MC/DC criterion.